Case Based Approach in Pharmacology: A Novel Approach - Banerjee, Indrajit (Nepal Journal of Epidemiology, 2014)
Case Oriented approach in Pharmacology will be helpful to know/study all the basic science in an integrated manner. This approach is a better approach so that the medical student will get the clinical scenario in the beginning of the topic. It will be also be effective tool for the students to solve the problem based questions and also they will learn the role of the clinical pharmacology too. Thus case oriented approach in teaching pharmacology will make Pharmacology more interesting subject. Recently based on certain evidences it was found out that basic science medical curriculum is based on clinical approach in which pharmacology is one integrated component in a holistic approach to teaching and learning methodology. One major problem of teaching pharmacology is that a student doesn’t see patients in basic science teaching and learning method. This problem can be solved to some extent by this novel case oriented approach in Pharmacology. DOI: http://dx.doi.org/10.3126/nje.v4i1.10125 Nepal Journal of Epidemiology 2014;4 (1): 301-305